THE EFFECT OF LEADERS’ MODEL ON THE TEACHERS’ WORK DISCIPLINE AT ELEMENTARY SCHOOLS IN KECAMATAN BONTOMARANNU KABUPATEN GOWA - Sahabuddin; Syarifuddin Sida, Idawati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Discipline is a condition which provides encouragements to someone to do and perform all activities following the norms or rules. The purpose of this study was to analyze and determine the effect of the leaders’ model on the teachers’ work discipline at elementary schools in Kecamatan Bontomarannu, Kabupaten Gowa. The population in this study was all elementary school teachers and principals at Kecamatan Bontomarannu, Kabupaten Gowa, consisting of 113 people from 18 schools with the status of Civil Servants (PNS). Considering the large population, the samples were chosen by random simple sampling resulting in 47 teachers and 18 principals taken as the samples. The results of this study were: 1) compensation, leaders’ model and the assertiveness of rules affected the teachers’ work discipline at elementary schools in Kecamatan Bontomarannu, Kabupaten Gowa. This was supported by the results of F test showing that the value of F-calculated was 47,352 with a significance value of 0,000 (< 0.05) at a significance level of 95% (α = 0.05). Thus, the factors of compensation, leaders’ model, and assertiveness were crucial to improve the teachers’ work discipline at elementary schools; 2) Compensation, leadership models, and assertiveness respectively affected the elementary school teachers’ work discipline; for example, compensation positively and significantly influenced for 0.212, the leaders’ model positively and significantly influenced for 0.342, the assertiveness positively and significantly influenced for 0.340, and those three factors significantly influenced the elementary school teachers’ work discipline in Kecamatan Bontomarannu, Kabupaten Gowa.